Pemanfaatan AI dalam Pembelajaran: Systematic Literature Review - Listiana, Listiana; Agustin, Sarah Tri; Fauziah, Muna; Awanis, Atsmarina (Universitas Sebelas Maret, 2025)
The development of AI technology that is increasingly developing requires all components of education, including teachers, to implement AI in learning optimally. This study attempts to examine and summarize previous research evidence on research trends on the use of AI in learning. This research is a type of systematic literature review research following the PRISMA rules. Data sourced from the Google Scholar database from 2022 to 2025. There are 30 articles that meet the criteria of this study. All data is analyzed in detail according to the guidelines. This study found that the research trend on the use of AI in learning was mostly carried out in China with a total of 10 studies (33.33%), followed by Turkey (16.67%), Spain (10%), Thailand (10%), the United States (6.67%), Indonesia (6.67%), Mexico, Malaysia, Germany, Finland, and Ukraine, each contributing a percentage of 3.33%. China is the most superior because China is the main center for exploring AI technology for education driven by large investments in research and digitalization of learning. Mixed-methods methods are the dominant type of research with a percentage of 33%, followed by qualitative methods (30%), quantitative (20%), quasi-experimental (10%), and case studies (7%). Students are the research subjects with the largest percentage of 45%, followed by teachers (23%), prospective teachers (6%), students (23%), and lecturers (3%). The research trend on the use of AI in learning is widely used to improve skills and learning outcomes as well as testing AI in learning with a percentage contribution of more than 20%. Meanwhile, topics from other categories such as psychology, technology, and long-term potential only contribute a percentage of less than 16%. Thus, it can be concluded that the trend of using AI in learning has been widely studied from various countries in the world such as China as the country that provides the largest contribution and focuses on mixed research at the tertiary level with a focus on improving student skills and learning outcomes.Perkembangan teknologi AI yang semakin berkembang mengharuskan seluruh komponen pendidikan termasuk guru untuk mengimplementasikan AI dalam pembelajaran secara maksimal. Penelitian ini berupaya untuk mengkaji dan merangkum bukti-bukti penelitian terdahulu tentang trend penelitian tentang pemanfaatan AI dalam pembelajaran. Penelitian ini merupakan jenis penelitian systematic literature review dengan mengikuti aturan PRISMA. Data bersumber dari database google scholar tahun 2022 hingga 2025. Terdapat 30 artikel yang sesuai dengan kriteria penelitian ini. Seluruh data tersebut dianalisis secara mendetail sesuai pedoman. Penelitian ini menemukan hasil bahwa trend penelitian tentang pemanfaatan AI dalam pembelajaran paling banyak dilakukan di China dengan jumlah 10 penelitian (33,33%), diikuti Turki (16,67%), Spanyol (10%), Thailand (10%), Amerika Serikat (6,67%), Indonesia (6,67%), Meksiko, Malaysia, Jerman, Finlandia, dan Ukraina yang masing-masing menyumbang persentase sebesar 3.33%.China menjadi yang paling unggul karena China menjadi pusat utama dalam eksplorasi teknologi AI untuk pendidikan yang didorong oleh investasi besar dalam riset dan digitalisasi pembelajaran. Metode mixed-methods menjadi jenis penelitian yang mendominasi dengan presentase 33%, disusul metode kualitatif (30%), kuantitatif (20%), quasi-eksperimen (10%), dan studi kasus (7%). Mahasiswa menjadi subjek penelitian dengan presentase terbesar sebanyak 45%, disambung oleh guru (23%), calon guru (6%), siswa (23%), dan dosen (3%). Trend penelitian tentang pemanfaatan AI dalam pembelajaran banyak digunakan untuk meningkatkan keterampilan dan hasil belajar serta pengujian AI dalam pembelajaran dengan sumbangan persentase lebih dari 20%. Adapun topik dari kategori lain seperti psikologi, teknologi, dan potensi jangka panjang hanya menyumbang persentase di bawah 16%. Maka, dapat disimpulkan bahwa trend pemanfaatan AI dalam pembelajaran telah banyak diteliti dari berbagai negara di dunia sebagaimana China sebagai negara yang memberikan sumbangan terbesar dan memfokuskan pada penelitian campuran pada jenjang perguruan tinggi dengan fokus pada peningkatan keterampilan dan hasil belajar mahasiswa.